PENGARUH PENGATURAN URUTAN MAKAN PROTEIN, SAYURAN, DAN KARBOHIDRAT TERHADAP GULA DARAH POST PRANDIAL PADA SUBJEK DEWASA SEHAT - Syahna Febby Windrati (2023)
Diabetes Mellitus (DM) is a general term used for a group of disease with metabolic disorders characterized by chronic hyperglycaemia. Modifiable risk factors for DM are included unhealthy diet pattern by controlling the meal order. Meal order is consuming macronutrient in a certain different order. The aim of this study is to analyse the effect of protein, vegetables, and carbohydrates meal order on post prandial blood sugar levels in healthy adult subject. The method used in this study was quasi experimental with cross-over study design. A total of 12 healthy adult subjects were participated in this study. All the participant were given 3 different treatments named consume carbohydrates before (Group 1), protein before (Group 2), and vegetable (Group 3). Glycaemic response was measured using finger prick method at 0, 30, 60, 90, and 120 minutes. The data showed that Group 1 had the highest glycaemic response. The result of ANOVA test result showed significant difference in the three groups at the 30th minutes (P<0,05) and Area Under Curve (AUC) showed significant difference of group 1 and 3 and lowest area was group 3. In conclusion there is a significant difference in meal ordering on the post prandial blood sugar.